IMPLEMENTASI PROGRAM KESEHATAN IBU DAN ANAK DI PUSKESMAS TETAP KABUPATEN KAUR - Elida, Yesmenti; Dani, Rahiman; Aprianty, Henny; Darmawi, Edi (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This research was conducted with the aim of analyzing the implementation of the Maternal and Child Health Program (KIA) at the Kaur Regency Permanent Health Center. The type of research used in this research is descriptive with a qualitative approach. This research is descriptive research which aims to collect information about current conditions and symptoms. Observation, interview and documentation techniques were used as data collection techniques. Data analysis techniques use data reduction, data presentation, as well as drawing and validating conclusions. The findings of this research indicate that: The implementation of the Maternal and Child Health (KIA) program at the Kaur District Health Center is going according to plan and is being implemented well and responsibly. This can be seen from the factors based on the theory of George Edward III. interact and influence policy implementation. Namely (1) the communication aspect of implementing the maternal and child health (KIA) support program at the Kaul Regency Permanent Health Center was very successful; Good and optimal. (2) The resource aspect of implementing the maternal and child health (KIA) service program at the Kaur Regency Permanent Health Center was successful. (3) dispositional aspects in the form of commitment and integrity, degree of democracy or information sharing; All duties of a political practitioner must be carried out with the same dedication and integrity that characterize a good democracy, and information must be shared openly. (4) The bureaucratic aspects of implementing the Maternal and Child Health (KIA) utility program at the Kaul Regency Permanent Health Center are adequate and on target.